2019
DOI: 10.3390/molecules24030613
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Polyester Fibers Dyed with Disperse Dyes for Forensic Purposes

Abstract: In forensic laboratories, the most commonly analyzed microtraces are microscopic fragments of single fibers. One of the main goals of the examination of fragments of fibers a few millimeters long is to determine their characteristic physicochemical properties and compare them with fibers originating from a known source (e.g., a suspect’s clothes). The color and dyes of fiber microtraces play an important role in their research and evaluation, being analyzed by means of microscopic, spectroscopic, and chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…MS allows for more specificity in differentiating dyes compared to LC alone, as response wavelength and retention time may be too similar to identify what compounds are present successfully. Furthermore, MS allows for the identification of substances at very low quantities, even when matrices are present and ionization suppression could affect the detection of all species [17,75–78].…”
Section: Identification and Characterization Of Synthetic Dyes With Mmentioning
confidence: 99%
See 1 more Smart Citation
“…MS allows for more specificity in differentiating dyes compared to LC alone, as response wavelength and retention time may be too similar to identify what compounds are present successfully. Furthermore, MS allows for the identification of substances at very low quantities, even when matrices are present and ionization suppression could affect the detection of all species [17,75–78].…”
Section: Identification and Characterization Of Synthetic Dyes With Mmentioning
confidence: 99%
“…In the case of disperse dyes, a common practice for analysis and identification is the use of LC or LC‐MS with the sample extracted from the fiber [17,77,79,100,101]; however, several studies have shown that dyes can be identified with direct ionization methods [7,74]. DART uses a stream of heated metastable gas to vaporize and ionize analytes, sending them directly into the mass spectrometer for analysis [7,85].…”
Section: Identification and Characterization Of Synthetic Dyes With Mmentioning
confidence: 99%
“…Various analytical techniques have been used to characterise and/or identify functional groups and particularly the azo group [14] in dye molecules. In general, analytical approaches include an extraction stage using low polarity solvents, such as chlorobenzene, methanol, dimethylsulfooxide, acetonitrile and dimethylformamide [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Different solvent mixtures were assessed and the best results were obtained with a mixture of ethanol and diethyl ether, which has not previously been reported as an extraction medium for medium-polarity azo dyes on polyesters fibres. Other studies have used more polar/toxic and/or complex mixtures of extractants [14]. The potential advantages of the reported analytical approach include the simplicity and rapid procedure of the extraction stage, the use of less toxic solvents, and only minimal amounts of both sample and extractant.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of disperse dyes by chromogen is significant for forensic analysts. Azo and anthraquinone disperse dyes are the main classes of disperse dyes in the market with the highest possibility of being subjected to forensic investigations [8]. Coumarin dyes have also gained recognition as one of the greatest commercially significant groups of fluorescent dyes having yellow with a green fluorescence as most commercial products.…”
Section: Introductionmentioning
confidence: 99%